Executives' excess compensation, legitimacy, and environmental information disclosure in Chinese heavily polluting companies: The moderating role of media pressure. (17th September 2018) - Li, Qiang; Li, Tian; Chen, Hongtao; Xiang, Erwei; Ruan, Wenjuan
Abstract: This study examines whether executives justify their excess compensation through environmental information disclosure using a sample of listed companies in China's heavily polluting industries from 2010 to 2014. We find that executives' excess compensation is positively related to the quality of environmental information disclosure. The above relationship is significant in cases with strong demand for compensation justification (i.e., state‐owned enterprises and firms where an internal compensation gap is salient), indicating that executives manipulate environmental information disclosure about their companies according to their purposes. We also find that media pressure weakens the above relationship. A further test affirms a differential influence of media pressure in settings that involve public or private ownership, development of markets, and low or high product market competition. This study reveals a self‐serving motive of executives for environmental information disclosure. The findings of this study have practical implications for regulators, shareholders, and managers.